2012
DOI: 10.1159/000334617
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Risk Factors in Patients with Premature Coronary, Supra-Aortic Branches and Peripheral Atherosclerotic Disease

Abstract: Objective: The aim of this study was to determine the distribution of major risk factors among patients with atherosclerotic disease aged ≤50 years. Subjects and Methods: The study population comprised 944 patients aged ≤50 years with clinically significant manifestations of atherosclerotic disease compared with 350 consecutive (control) older patients (age >50 years). Results: The most significant risk factors for atherosclerotic disease of the supra-aortic branches were: smoking (87.5%, p < 0.001), family hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
4
0
2
Order By: Relevance
“…Smoking is a relevant risk factor for all types of IHD, but its importance has been reported particularly in the setting of premature atherosclerosis [37]. In a population of almost 1000 patients (≤ 50 years) with clinically significant manifestations of atherosclerosis, cigarette smoking was the most common preventable risk factor [37]. However, data are scarce on COPD prevalence in this setting.…”
Section: Putative Shared Risk Factors That Sustain Low-grade Systemicmentioning
confidence: 99%
“…Smoking is a relevant risk factor for all types of IHD, but its importance has been reported particularly in the setting of premature atherosclerosis [37]. In a population of almost 1000 patients (≤ 50 years) with clinically significant manifestations of atherosclerosis, cigarette smoking was the most common preventable risk factor [37]. However, data are scarce on COPD prevalence in this setting.…”
Section: Putative Shared Risk Factors That Sustain Low-grade Systemicmentioning
confidence: 99%
“…The other studies also confirmed the predominant effect of smoking habits on PAD occurrence in comparison to the other vascular beds of atherosclerosis manifestation. In a study by Radak et al [27] the most significant risk factors for PAD were smoking (97%), hyperlipidemia, and a family history of atherosclerotic disease. In work by Agarwal and Naderi [28], in comparison with CAD patients, subjects with PAD were more frequently female, black, and active smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Із загальних чинників ризику, які можуть викликати сис-темне запалення, найбільш поширеним є куріння -ініцію-ючий чинник запальної реакції у багатьох сприйнятливих осіб, у яких розвивається ХОЗЛ, а також основний фактор ризику розвитку ССЗ [27]. Кожна цигарка містить понад 2000 ксенобіотичних сполук і 10 вільних радикалів.…”
Section: Issn 2306-4145unclassified
“…Так, при обстеженні 1000 пацієнтів віком ≤ 50 років із клінічно значущими проявами атероскле-розу куріння було найбільш поширеним, але модифікованим фактором ризику [27]. Втім, сьогодні недостатньо даних про поширеність ХОЗЛ у цієї категорії пацієнтів.…”
Section: Issn 2306-4145unclassified